Zon - Gyssels, Willem; Schoemaker, Maurits (Berchem : De Ring, 1935)
Bibliotheek Camille Huysmans
Dedicator: Schoemaker, M., dedicatee: Huysmans, Camille
Nederlands
Partituur
Keywords: partituren; liederen